Political Marketing Mix in Indonesia Parties - Simbolon, Freddy (Binus Business Review, 2016)
The reform era has changed the paradigm of Indonesian politics. Multiparty system has demanded a political partyÂ to be able to compete for their constituents. Article aimed to convey a political marketing concept that can helppolitical parties in planning a strategy to win the election. Research method used descriptive method analysis. TheÂ results suggest that the approach of the marketing mix that includes the product, price, place, and promotion areapproaches that are very helpful in presenting a plan to win the marketing strategy of political parties in elections.